Legal Reform Perspectives on the Protection of Wives in Unregistered Marriages - Rifqi, Pramidazzura Alifa; Samsidar; Zulfiani (Ipso Jure, 2026)
Unregistered marriage remains a prevalent practice in Indonesia and poses serious legal vulnerabilities for wives. Although Indonesian marriage law emphasizes compulsory registration to ensure legal order, it fails to provide substantive legal protection for wives when registration is not fulfilled. This normative gap places wives in unregistered marriages in a legally precarious position, depriving them of legal recognition, civil rights, and effective protection. This study employs a normative juridical method with statute, conceptual, and case approaches to analyze the weaknesses of legal protection for wives in unregistered marriages and to formulate legal reform perspectives. The findings indicate that the current legal framework prioritizes administrative legality over substantive justice, resulting in gender-based legal inequality. The absence of alternative protection mechanisms reinforces structural vulnerability and limits access to justice for wives. Therefore, legal reform is required to shift from a purely legal-formal paradigm toward substantive protection by recognizing and safeguarding certain civil rights of wives regardless of registration status. Strengthening the role of religious courts and integrating human rights and gender equality perspectives are essential to ensure fair and effective legal protection. Such reforms are necessary to align marriage law with constitutional guarantees of legal certainty, protection, and justice.